Características clínico epidemiológicas de las complicaciones postoperatorias asociadas al tiempo operatorio en la cirugía de catarata con la técnica de faco-emulsificación en el período febrero 2018 – enero 2019 - Ramírez Malatesta, Diego (2019)
Objective: To indicate the clinical and epidemiological characteristics of the cases of complica-tions associated with the operative time in patients undergoing cataract surgery with the phacoemulsification technique in the period February 2018 - January 2019 Materials and methods: A descriptive observational study in which all patients undergoing phacoemulsification surgery in the Ophthalmology service of the Hospital Victor Lazarte Ech-egaray in the period February 2018 - January 2019 will be analyzed. Patients will be distribut-ed according to the surgery time, and to the energy dissipated during the surgery and the postoperative findings such as intraocular pressure, pain, corneal edema, endophthalmitis, hyphema, cystoid macular edema; to find correlations between these and the surgery time.